Implementasi Sistem Informasi Desa di Kabupaten Bekasi - Abdul Shomad (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2018)
The implementation of village information systems by village governance is a necessity. The obligation to implement a village information system is regulated in Law Number 6 of 2014 concerning Villages. Indeed, the village information system makes it easy for the community and other stakeholders to access village data, village development and rural development. Implementation of the roles of government, programs, and village budgets becomes transparent. The accountability of implementing the government becomes more accountable. This study intends to determine the extent of understanding of the Village Head or Village Apparatus in understanding Law No. 6 of 2014 concerning Villages and how seriously the Village Head or Village Apparatus implements the Village Information System. This study applied mix-methods/combined quantitative and qualitative with the acquisition of data through survey and in-depth interviews. The results of this study found that the application of the village information system was not fully optimal. There are still villages that do not have village data and do not give access to the community to see budgets, work programs and other village policies. In fact, it is even more ironic, there are still village officials who do not know about the Village Law, even whether they only hear the name.